Route/Modal choice analysis and tradeoffs evaluation of the intermodal transport network of Peninsular Malaysia - Gohari, A. (Cogent OA, 2018)
In Malaysia, containerized freight transport has been growing and is expected to continue in that trend in the future. This research aims to provide a model for the assessment of containerized freight movement through intermodal transport network of Peninsular Malaysia. To design such a model, ArcMap software was used to build the transport network and MATLAB software was used to design the user-interface and to develop shortest path algorithm for analyzing the transport network. The focus of the analysis was to identify the optimum route and mode(s) of transport from origin to destination for different objective functions such as distance, time, emission and cost. Besides, the study explored tradeoffs associated with least-distance, least-time, least-emission and least-cost routes. To demonstrate the applicability of the proposed model, two case studies were analyzed. The presented methodology and procedures are applicable not only on any origin-destination pair in the transport network of Malaysia, but also on any other intermodal transport networks. Â© 2018 The Author(s). This open access article is distributed under a Creative Commons Attribution (CC-BY) 4.0 license.